Lethal Dose, Clinical Signs, Gross and Microscopic Lesions Induced by Aeromonas veronii Biovar sobria A4 Strain in Experimentally Challenged Nile Tilapia (Oreochromis niloticus) - Joseph M. Ndegwa; Isaac R. Mulei; Lucy W. Njagi; Philip N. Nyaga; Daniel W. Wanja; Shimaa E. Ali; Jérôme Delamare-Deboutteville (Veterinary Medicine International)
Aeromonas veronii biotype sobria is a potential aquatic zoonotic pathogen and a major cause of freshwater bacterial infections in cultured fish globally, leading to substantial economic losses. This study aimed to establish the median lethal dose (LD50-96 h) for Aeromonas veronii biovar sobria A4 strain and to demonstrate induction of clinical signs, gross and microscopic lesions in experimentally infected juvenile Nile tilapia (Oreochromis niloticus). Aeromonas veronii biotype sobria A4 strain used in this study were obtained from water samples from ponds with high fish mortality at Cavarino farm in Narok County, Kenya. Six groups each comprising 10 fish were intraperitoneally injected with 0.1 mL of A. veronii biovar sobria A4 strain suspension at: 1.5 × 104, 1.5 × 105, 1.5 × 106, 1.5 × 107, 1.5 × 108, and 1.5 × 109 colony forming units per mL (CFU/mL) respectively and the bacteria was afterward recovered from kidney and hepatopancreas of freshly dead fish. Duplicate control groups (each n = 10) were injected with sterile physiological saline before the lethal dose group were injected with varying concentration of the A. veronii biovar sobria A4 strain. The LD50-96 h of A. veronii biovar sobria A4 strain was found to be 1.5 × 108 CFU/mL. Clinical signs and gross lesions observed in the lethal dose group were: skin hemorrhages (20%), erosion of the fins including caudal fin with scale loss exposing underlying skin (13.7%), congested and hemorrhagic gills (15%), hepatic hemorrhages and enlargement (21.3%), distension of gall bladder (18.8%), splenomegaly and congestion (22.5%), and ascites (16.3%). The main histopathological lesions observed in the gills were focal hemorrhages, atrophy of the filaments and loss of lamellae in some filaments with mononuclear cellular infiltration; on the liver there were; hemorrhages, infiltration with lymphocytes and melanomacrophages, degenerative hepatocytes and focal necrosis. There was extensive hemosiderosis with increased melanomacrophages in the spleen. The kidney showed extensive hemorrhages, localized coagulative necrosis, atrophied glomeruli and multifocal mononuclear cellular infiltration in the interstitium. The findings will lay a foundational basis for subsequent investigations into the host-pathogen interaction, therapeutic approaches, and epidemiology of Aeromonas veronii biovar sobria.